Biology and predatory potential of green lacewing (Apertochrysa sp.) - Ali Hussain, Mohammed A. (2010)
The green lacewings being active polyphagous predatos, can be mass reared in the laboratory and used for classical, inundative and augmentative release against crops pests. The green lacewings are also resistant to wide range of pesticide and one of the most important biological control agents in integrated pest management. The studie were conducted at University Putra Malaysia (UPM), to establish the laboratory culture of Apertochrysa sp. The studies comprised of the following new and original contIibutions: 1- Identified the important species of green lacewing and surveyed the OCCUlTenceof Apertochrysa sp. in field and within the plants 2- Studied the effect of temperature and type of prey on survival and development time of immature stages 3- Established nest of life table studies 4- Determined axon of the functional responses 5- Studied the effect of storage on eggs and pupae, and 6- Determined the effect of insecticides on different stages of Apertochrysa sp. A total of 43 local plants were surveyed and only 18 plants were found with eggs of Apertochrysa sp. The citrus trees showed the highest number of eggs of Apertochrysa sp. recorded, 65.84% (4 eggs/ plant). The Telenomus sp. was highly affecting the eggs of Apertochrysa sp. and the highest parasitism was recorded on the eggs collected from com plants (14%), while the parasitism was 9.2% on eggs collected from citrus trees. No significant differences between the heights (0-1 m, 1-2 m and 2-3 m) above the ground on occurrence of eggs, but the east side recorded 79.8% of laid eggs, which seemed to be more attractive to the females of Apertochrysa sp. for oviposition. In sweet com,100% of eggs were found on the height of 1-2 m above the ground, and no significant differences on the number of eggs laid between the east and west side of the plant. The number of eggs of Apertochrysa sp. was found to be significantly different on the lower and upper surface of the citrus and com leaf. At 60 days after planting of sweet com the number of eggs of Apertochrysa sp. was found to be the highest. The larval developmental times of Apertochrysa sp. at15°C, 20°C, 25°C, and 28±3°C (laboratory condition) were 50.54, 41.9, 11.3, and 15.7 days respectively, and the total developmental times from egg to adult were 88.36, 68.8, 29.5 and 33.3 days respectively. The Apertochrysa sp. was successfully cultured and complete it's life cycle on Corcyra cephalonica eggs, Rapolasiphum maidis, Aleurodicus disperses Russell and Aleurocanthus woglumi Ashby and the total developmental times were 29.5, 25.4, 22.8 and 30 days respectively. The survivorship (Ix) of Apertochrysa sp. for three different cohorts indicates to high mortality occurring during eggs, larvae (particularly 2nd instal') and pupae. The intrinsic rate of natural increase (r) was 0.02 (females / female / day) with mean generation time (T) was 40.6 days. The net reproductive rate (RO) of the population was 2.3. The population double time (DT) was within 14.8 clays. The highest number of aphids, R. maidis, was consumed by the third instar larva (42.95 aphids/ larva), followed by second instar (36 aphids/ larva), then the first instar (31.14 aphids/ larva). While the eggs of C. cephalonica were consumed by first, second and third instar of larvae of Apertochrysa sp. are 68.4, 232.1, 494.6 eggs/larva respectively. The longest storage period of eggs of Apertochrysa sp. was 9.49 days at 15°C followed by 7.31 days at 20°C. While the pupae following 20 days of storage at 20°C showed the lowest mortalitv (16.2%) with good percentage of good quality adults produced (67.52%). However the pupae stored at 15°C for 40 days gave 100% disability. The four insecticides (carbaryl, cypermethrin,azadirachtin, and imidacloprid) tested on eggs of Apertochrysa sp. in the laboratory showed slightly harmful effect with eggs mortality ranged from 43.33% to 63.33%. When the insecticides were treated on the third instars larvae, the mortality at 72h was less than 13.33% and all insecticides were categorized as harmless. The effect based on successful pupation was categorized as harmless also for carbaryl (7% mortality),cypermethrin (l0% mortality), azadirachitin (23.15% mortality) and imidacloprid (25.92% mortality). Based on the successful molt to adults of the treated third instars larvae, cypermethrin ,azadirachitin and imidacloprid were harmless while carbaryl was harmful. The insecticides when treated on pupae showed harmless effect (mortality .:s 20%), however,when the effect was based on the successful molting to adults from the treated pupae, azadirachitin (10% mortality) was harmless, slightly harmful for cypermethrin (50%mortality) and imidacloprid (56.7% mortality) and harmful for carbaryl (100% mortality). All four insecticides recorded harmful effect (100% mortality) when treated on the adults of Apertochrysa sp. within 72h. The newly recorded green lacewing Apertochrysa sp. is an important predator in Malaysian agro-ecosystem environment. High tolerance to insecticides, high potential on different insect pest and successfully mass culture of Apertochrysa sp. in laboratory make it a good biological control agent can be used to control different lepidopteran and homopteran pests.